Viral Marketing : Need Of The Hour (Trinity Journal of Management, IT & Media (TJMITM), 2016)
Marketers have been using electronic tools for many years, but the  Internet and other new technologies created a flood of interesting  and innovative ways to provide and enhance customer value.  Not only did this challenge the fundamental basics of traditional  marketing, but it also helped to shape the practice of modern  marketing The advancement of technology has not only created  new ways for marketers to spread information, but also enabled  consumers to spread information on-line or through other digital  mediums that challenge traditional marketing practices. Since  viral marketing is still a new and unexplored concept for most  of the markets, it is the purpose of this article to determine if it is  not just another buzzword. To establish if marketers can practice  viral marketing, the concept of viral marketing is clarified before  addressing more specific issues related to it. We present an  analysis of a person-to-person recommendation network, on a lot  of products. We observe the propagation of recommendations and  the cascade sizes, which we explain by a simple stochastic model.  We analyze how user behavior varies within user communities  defined by a recommendation network. Product purchases follow  a ’long tail’ where a significant share of purchases belongs to  rarely sold items. We establish how the recommendation network  grows over time and how effective it is from the viewpoint of the  sender and receiver of the recommendations. While on average  recommendations are not very effective at inducing purchases  and do not spread very far, we present a model that successfully  identifies communities, product and pricing categories for which  viral marketing seems to be very effective.
Keywords: traditional marketing; modern marketing; recommendation network